Prevalence of a history of prior varicella/herpes zoster infection in multiple sclerosis - Manouchehrinia, Ali; Tanasescu, Radu; Kareem, Huner; Jerca, Oltita P.; Jabeen, Fouzia; Shafei, Rachelle; Breuer, Judith; Neal, Keith R.; Irving, William L.; Constantinescu, Cris S. (Springer, 2017)
Varicella zoster virus (VZV) infection has been implicated in multiple sclerosis (MS), but direct causal involvement has been disputed. Nevertheless, knowledge of VZV exposure is important, given the risk of serious complications of first exposure while undergoing immunosuppressive treatment, in particular with fingolimod. We distributed questionnaires to MS clinic patients, requesting information about history of chickenpox, sibling/household/occupational exposure, history of zoster (shingles), and disease-modifying treatment. A random, proportionally representative sample of 51 patients that included patients with positive, negative, and unknown chickenpox history were selected for determination of VZV IgG by ELISA. Of 1206 distributed questionnaires, 605 were returned (50% response rate). Of these, 86% reported history of chickenpox, 5.6% gave negative history, and 8.5% did not know. Of 594 who answered the zoster question, 78% gave a negative response, 4% did not know, and 104 (17%) answered yes. Of these, 83 reported 1 episode; 12 had 2; 5 had 3; and 1 each reported 5, 6, and 15 episodes. Of 51 patients tested for VZV IgG (44 “yes,” 4 “no,” and 3 “I don’t know” answers to the question of whether they had chickenpox), 48 were seropositive; the 3 seronegative all had reported having had chickenpox. The high rate of MS patients reporting prior chickenpox infection is comparable with previous reports. A substantial proportion of MS patients, estimated to be higher than an age-matched general population, report single or multiple episodes of zoster. These data are useful for consideration of immunosuppressive treatments and/or VZV and zoster vaccination.